2009
DOI: 10.1111/j.1469-7610.2009.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression begets depression: Comparing the predictive utility of depression and anxiety symptoms to later depression

Abstract: Background-The high comorbidity between depressive and anxiety disorders, especially among females, has called into question the independence of these two symptom groups. It is possible that childhood anxiety typically precedes depression in girls. Comparing of the predictive utility of symptoms of anxiety with the predictive utility of symptoms of depression from early childhood to early adolescence is needed to test this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
89
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 22 publications
7
89
1
Order By: Relevance
“…Previous studies have documented both homotypic 611 and heterotypic continuity 7, 1219 in a range of common forms of psychopathology during childhood and adolescence. There has been little study of heterotypic continuity of mental disorders during adulthood, however.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have documented both homotypic 611 and heterotypic continuity 7, 1219 in a range of common forms of psychopathology during childhood and adolescence. There has been little study of heterotypic continuity of mental disorders during adulthood, however.…”
mentioning
confidence: 99%
“…In these first analyses, heterotypic continuity will be demonstrated only when disorder X at time 1 ( X1 ) predicts disorder Y at time 2 ( Y2 ) when disorder Y at time 1 ( Y1 ) is controlled. 11 This analysis ensures that X1 does not predict Y2 solely because X and Y are correlated at both time points.…”
mentioning
confidence: 99%
“…That is, not only are the two types of disorder frequently comorbid during adolescence (Kessler et al 2001), but there is a tendency for each to be preceded by the other (Kovacs et al 1989;Moffitt et al 2007). Although there have been challenges to the heretofore prevailing view that anxiety disorders tend to precede depressive disorders, longitudinal findings on the two types of symptoms indicate that anxiety symptoms contribute to changes in depressive symptoms even when previous depressive symptoms are taken into account (Keenan et al 2009). Given these various forms of overlap between depression and anxiety, developmental psychopathologists have argued that depression and generalized-type anxiety can be considered forms of a more general distress disorder (Moffitt et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, using growth modeling, Edgerton and colleagues (2014) found that gambling problems tend to decrease over time in young adults (i.e., from ages 18 to 24 years). More studies have modeled changes in depressive symptoms across adolescence (Cole et al, 2002;Garber, Keiley, & Martin, 2002;Keenan, Feng, Hipwell, & Klostermann, 2009;Measelle, Stice, & Hogansen, 2006) and from adolescence to early adulthood (Galambos, Barker, & Krahn, 2006;Galambos, Leadbeater, & Barker, 2004;Ge, Lorenz, Conger, Elder, & Simons, 1994;Kim, Capaldi, & Stoolmiller, 2003). These studies have consistently found that levels of depressive symptoms are rather low during middle childhood but increase significantly over the course of early adolescence, albeit mainly in girls.…”
Section: Latent Trajectory Classes Of Problem Gamblers And-or Depressmentioning
confidence: 97%